Pd Seed Under-layer Effect on Coercive Field of Perpendicularly Magnetized Co/Pd Multilayer Films - Budi Purnama (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2010)
Coercive field, Hc dependence of Pd seed under layer has been investigated for Co/Pd multilayer with perpendicular anisotropy magnetic. Structured Co/Pd multilayer fabricated by DC sputtering machine on glass substrate. Results indicated that Pd seed under layer of 50Å thicknesses successfully increased Hc from 800Oe to 1600Oe. The results could be related to the Co/Pd multilayered grain to grow separately leading exchange de-coupling effect, beside the increase of surface interaction.